2019
DOI: 10.3390/pharmaceutics11090435
|View full text |Cite
|
Sign up to set email alerts
|

Electrospray-Based Microencapsulation of Epigallocatechin 3-Gallate for Local Delivery into the Intervertebral Disc

Abstract: Locally delivered anti-inflammatory compounds can restore the homeostasis of the degenerated intervertebral disc (IVD). With beneficial effects on IVD cells, epigallocatechin 3-gallate (EGCG) is a promising therapeutic candidate. However, EGCG is prone to rapid degradation and/or depletion. Therefore, the purpose of this study was to develop a method for controlled EGCG delivery in the degenerated IVD. Primary IVD cells were isolated from human donors undergoing IVD surgeries. EGCG was encapsulated into microp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…Gelatin‐pectin‐essential oil nanoparticles have a spherical shape and are well dispersed. The globular shape of nanoparticles makes them the most capable of controlled release and protects the payloads because the spherical shape has the longest path to the movement of the entrapped extract in the nanoparticles and also the lowest contact area with the dispersed phase aqueous medium compared to other forms of nanoparticles (Loepfe et al., 2019). The extracted plants essential oils did not have a significant impact on the topology of the particles but improved their biological activity.…”
Section: Resultsmentioning
confidence: 99%
“…Gelatin‐pectin‐essential oil nanoparticles have a spherical shape and are well dispersed. The globular shape of nanoparticles makes them the most capable of controlled release and protects the payloads because the spherical shape has the longest path to the movement of the entrapped extract in the nanoparticles and also the lowest contact area with the dispersed phase aqueous medium compared to other forms of nanoparticles (Loepfe et al., 2019). The extracted plants essential oils did not have a significant impact on the topology of the particles but improved their biological activity.…”
Section: Resultsmentioning
confidence: 99%
“…However, the stability of EGCG is susceptible to its environment (enzymes, temperature, pH), and therefore it is difficult to maintain high biological activity ( Krupkova et al, 2016a ). Based on this concern, a team produced large quantities of gelatin microspheres loaded with EGCG by a modified electrospray technique and systematically validated them in vitro ( Loepfe et al, 2019 ). Coculture with IVD cells in 3D alginate constructs showed that EGCG-GM had excellent biocompatibility and significantly inhibited the expression of IL-1β-induced inflammatory factors (IL-6, IL-8, and COX-2) and catabolic mediators (MMP-1, -3, and -13).…”
Section: Application Of Microsphere-based Delivery Systems In Ivddmentioning
confidence: 99%
“…In summary, EGCG encapsulation based on electrospraying leads to microparticle cytocompatibility that preserves EGCG activity and shows potential for controlling EGCG release by downregulating localized inflammation. [125] Liu et al developed an aspirin (ASP)-loaded hydrogel by mixing ASP-liposomes with photocrosslinkable gelatin-methacryloyl (GelMA; together termed ASP-Lip@GelMA). The ASP-Lip@GelMA hydrogel upregulated aggrecan and collagen II, whereas decreased ADAMTS reduced MMPs by restraining HMGB-1 release.…”
Section: Microspheresmentioning
confidence: 99%